2010
DOI: 10.1111/j.1439-0450.1980.tb01651.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Flora of the Respiratory Tract of Wild Birds in Ludhiana (Punjab)

Abstract: Die Bakterienflora des oberen Respirationstraktes wild lebender Vogel in der Umgebung von Farmen in der Gegend von Ludhiana (Punjab, Indien) wurde untersucht. Von den 100 untersuchten Vogeln waren 63 Trager verschiedener Bakterienarten und insgesamt wurden 79 Bakterienstamme, die 16 verscfiiedenen Spezies angehorten, aus der Laryngo-Tracheal-Gegend dieser Tiere isoliert. Das Vorherrschen von pathogenen Bakterienarten wie Staph. aureus, Corynebacterium, Erysipelothrix, Klebsiella, Esch. coli, Pseudomonas und Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…are opportunistic diarrhea causes pathogens in poultry. Sambyal and Baxi (1980) Studies have shown that E. coli, a normal habitat of human and animal intestines, when constantly gets exposed to antibiotics; it develops resistance in order to survive. When these resistant isolates are excreted to the environment by faeces, they tend to spread resistance genes by vertical gene transfer to pathogens (Sorum and Sunde, 2001;Richard and Yitzhak, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…are opportunistic diarrhea causes pathogens in poultry. Sambyal and Baxi (1980) Studies have shown that E. coli, a normal habitat of human and animal intestines, when constantly gets exposed to antibiotics; it develops resistance in order to survive. When these resistant isolates are excreted to the environment by faeces, they tend to spread resistance genes by vertical gene transfer to pathogens (Sorum and Sunde, 2001;Richard and Yitzhak, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…and Pasteurella spp. (Sambyal and Baxi, 1980). There are many factors that predispose the respiratory tract infections by the normal bacterial flora.…”
Section: Introductionmentioning
confidence: 99%